2017
DOI: 10.1016/j.ajpath.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of Calcineurin 3 Ameliorates Autoimmune Arthritis by Suppressing Th17 Cell Differentiation

Abstract: Regulator of calcineurin 3 (RCAN3), an endogenous regulator of the calcineurin-nuclear factor of activated T cells (NFAT) signaling pathway, inhibits the phosphatase activity of calcineurin, the nuclear translocation of NFAT, and the NFAT downstream pathway. To investigate the effects of RCAN3 on T-cell regulatory function and the development and progression of inflammatory arthritis, we studied the effects of RCAN3 transfection on regulation of Th17 cell differentiation in a murine T-lymphoma cell line and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The CIA was generated as described previously . On day 7 after the first immunization, mice were injected intravenously with 100 μg of p3XFLAG‐CMV‐10‐CRIF1 or control vector in 2 ml of saline within 5 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The CIA was generated as described previously . On day 7 after the first immunization, mice were injected intravenously with 100 μg of p3XFLAG‐CMV‐10‐CRIF1 or control vector in 2 ml of saline within 5 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The genes and their corresponding lncRNA-related osteogenesis, cell proliferation, and migration were randomly selected to construct a network diagram. RCAN3, is a calcineurin that affects osteoclasts and participates in osteoclast differentiation 31 . CSF1 is one of the cytokines directly involved in osteoclast differentiation, which could actively regulate the proliferation, differentiation These results revealed that the lncRNAs and genes were differentially expressed in mesenchymal and cartilage tissue, which was consistent with the results of high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…RCAN3 was a favorable prognostic biomarker while PTPRJ was an unfavorable marker in PCPG. RCAN3 not only may be involved in immune response as an endogenous regulator of the calcineurin-nuclear factor of activated T cells (NFAT) signaling pathway, 29 but also plays a vital role in suppression of cancer. 30 PTPRJ, also named CD148, could negatively regulate T-cell activation and play a role in feedback inhibition of T-cell immune responses, 31 which may result in a poor prognosis in PCPG.…”
Section: Dovepressmentioning
confidence: 99%